Chapter Lake Garda lemon houses: a mediterranean landscape in an internal lake - CAZZANI, ALBERTA (Proceedings e report, 2020)
Lemon houses (limonaie) are ancient terraced citrus gardens that shape the landscape along the NW shore of Lake Garda (Northern Italy). We propose an interpretation of limonaie as a deeply anthropogenic, labour intensive, multifunctional landscape that shares many characteristics with the oases of the wider Mediterranean basin. Any intervention which aims at preserving the fragility and peculiarity of the area, as well as the intangible cultural heritage of the citrus cultivation, should be framed in a holistic agroecosystemic perspective, deeply rooted in the knowledge of the limonaie past.